Analisis Kondisi Eksisting Jaringan Pipa Distribusi Air Bersih Kelurahan Simpang Rumbio, PDAM Kota Solok - Ridwan Ridwan (Fakultas Teknik, 2019)
This research is intended to determine the hydraulic conditions of the clean water distribution network in Simpang Rumbio Village by Solok City PDAM, in order to resolve water problems that often do not flow in the city border area and its surroundings. PDAM Solok City must be able to meet customers’ clean water needs from aspects of quality, quantity and continuity. From the data of active customers of PDAM Kota Solok in 2018, the average level of clean water usage is 806 liters / customer / month or 130 liters / person / day, with an average water loss rate of 43.17%. The nodes included in Epanet 2.0 Software are 7 nodes, with the initial node P being a reservoir equipped with a capacity distribution pump of 30 liters / second and a head of 60 meters around the CEC IPA area. The six other nodes are the point of collection for active customers in Simpang Rumbio Subdistrict as many as 1,547 customers with a total distribution pipe length of 6,300 meters Epanet 2.0 analysis results, there is a negative pressure on node 5 (Prosecutor’s Office) (-0.18) meters and node 6 (Saok Laweh) (-4, 5) meters. The alternative solution is by replacing pipe 4 from a diameter of 100 mm to 150 mm type PVC, or increasing the specifications of the pump head to 70–80 meters